Separator for secondary battery, method for producing same and secondary battery
The secondary battery separation film with a functional coating layer using inorganic particles, acrylic binders, and polydopamine addresses thermal instability issues, ensuring safety and performance by preventing heat contraction and electrode exposure.
Patent Information
- Application Number
- JP2024539920
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-20
- Filing Date
- 2023-10-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-10-23
AI Technical Summary
Secondary batteries face safety issues at high temperatures due to internal short circuits and thermal instability, leading to potential explosions and ignition, which current separation films fail to adequately address.
A secondary battery separation film with a functional coating layer comprising a porous substrate and multiple coating layers, including inorganic particles, acrylic binders, and polydopamine, which enhances dimensional stability and ionic conductivity, preventing heat contraction and electrode exposure.
The film improves dimensional stability and ionic conductivity, effectively preventing thermal contraction and electrode exposure under high temperature conditions, thereby enhancing safety and performance of secondary batteries.
Smart Images

Figure 2025502841000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention claims the benefit of the filing date of Korean Patent Application No. 10-2022-0136805 filed with the Korean Intellectual Property Office on October 21, 2022, and Korean Patent Application No. 10-2023-0141362 filed with the Korean Intellectual Property Office on October 20, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a separator for a secondary battery, and more particularly to a separator for a secondary battery, a method for producing the same, and a secondary battery. [Background technology]
[0003] Lithium ion batteries, a representative example of secondary batteries, are basically composed of a positive electrode, a separator, a negative electrode, and an electrolyte, and are a representative energy device with high energy density that can be charged and discharged while reversibly converting chemical energy and electrical energy. They are widely used in small electronic devices such as mobile phones and laptops.
[0004] Recently, in response to environmental issues, high oil prices, and energy efficiency and storage, the application of lithium-ion batteries to hybrid electric vehicles (HEVs), plug-in electric vehicles (Plug-in EVs), electric bikes (E-bikes) and energy storage systems (ESSs) is expanding rapidly. Lithium-ion batteries are stable electrochemical devices insulated by a separator, but internal or external abnormal battery phenomena or impacts can cause a short circuit between the positive and negative electrodes, which can lead to heat generation and explosion, so ensuring the thermal and chemical safety of the separator as an insulator is a matter that must be considered with the utmost importance.
[0005] One of the main research topics for secondary batteries is to improve their safety at high temperatures. For example, secondary batteries may explode due to high temperatures and pressures inside the battery caused by abnormal operating conditions of the battery, such as internal short circuits, overcharging exceeding the allowable current and voltage, exposure to high temperatures, deformation due to dropping or external impact, etc. Internal short circuits caused by contraction or damage of the separator when the battery is exposed to high temperatures are currently very serious, and much research is being conducted to identify the causes and find alternatives.
[0006] Meanwhile, when a battery cell is stored at a high temperature, there is a risk of fire due to the possibility of an internal short circuit occurring due to the contraction of the separator, and excessive coating to prevent this can cause problems such as insufficient capacity of the battery cell, increased resistance of the battery cell, and an increase in the thickness of the battery cell. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a separator for a secondary battery which has excellent dimensional stability even at high temperatures when in a wet state with an electrolyte injected therein.
[0008] Another object of the present invention is to provide a separator for a secondary battery capable of increasing the loading amount of polydopamine.
[0009] It is yet another object of the present invention to provide a separator for a secondary battery capable of increasing the ionic conductivity of lithium ions.
[0010] It is yet another object of the present invention to provide a method for manufacturing the separator for a secondary battery.
[0011] It is yet another object of the present invention to provide a secondary battery including the separator for secondary batteries.
[0012] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and will be more clearly understood by the embodiment of the present invention. Also, it should be easily understood that the object and advantages of the present invention can be realized by the means and combinations thereof as set forth in the claims. [Means for solving the problem]
[0013] In order to achieve the above object, a first aspect of the present invention provides a separator for a secondary battery, comprising: a porous substrate; and a functional coating layer disposed on at least one surface of the porous substrate, the functional coating layer comprising a first coating layer and a second coating layer disposed on the first coating layer, the first coating layer comprising inorganic particles, an acrylic binder, and polydopamine, and the second coating layer comprising polydopamine.
[0014] According to a second aspect of the present invention, in the first aspect, at least one surface of the porous substrate may be coated with polydopamine.
[0015] According to a third aspect of the present invention, in the first or second aspect, the second coating layer may be made of polydopamine.
[0016] According to a fourth aspect of the present invention, in any one of the first to third aspects, the polydopamine of the first coating layer may be coated on a surface of at least one of the acrylic binder and the inorganic particles.
[0017] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the first coating layer may have a thickness of 0.1 to 5 μm, and the second coating layer may have a thickness of 0.005 to 0.05 μm.
[0018] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the decomposition temperature (T d ) may be from 280 to 320°C.
[0019] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the glass transition temperature (T g ) may be from -20 to 80°C.
[0020] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the weight average molecular weight (M w ) can be from 100,000 to 2,000,000 g / mol.
[0021] According to a ninth aspect of the present invention, there is provided a method for manufacturing a separator for a secondary battery, comprising: (S1) immersing a preliminary separator including a porous substrate and a first coating layer disposed on at least one surface of the porous substrate in a dopamine precursor solution for 4 to 50 hours; and (S2) adjusting an amount of dissolved oxygen in the dopamine precursor solution in which the preliminary separator is immersed to form a second coating layer on at least one surface of the preliminary separator, wherein the dopamine precursor solution has a pH of 7 to 10, and the first coating layer includes an acrylic binder.
[0022] According to a tenth aspect of the present invention, in the ninth aspect, the amount of dissolved oxygen contained in the dopamine precursor solution in which the preliminary separation membrane is immersed may be 8.0 to 11.0 ppm.
[0023] According to an eleventh aspect of the present invention, there is provided a secondary battery including a negative electrode, a positive electrode, a separator for a secondary battery according to any one of the first to eighth aspects interposed between the negative electrode and the positive electrode, and an electrolyte.
[0024] The above-mentioned solutions to the problems are not exhaustive, and various features of the present invention and their attendant advantages and effects will be more fully understood with reference to the following specific embodiments. Effect of the Invention
[0025] According to one aspect of the present invention, a separator for a secondary battery that improves dimensional stability at high temperatures when in a wet state after an electrolyte is injected by increasing the loading amount of polydopamine can be provided. When a secondary battery is realized using such a separator for a secondary battery, the problem of electrodes being exposed due to thermal shrinkage of the separator under high temperature conditions can be solved.
[0026] The specific effects of the present invention, together with the above-mentioned effects, will be described below while explaining the specific contents for carrying out the invention. [Brief description of the drawings]
[0027] [Figure 1] 1 is a cross-sectional view of a separator for a secondary battery according to an embodiment of the present invention.
[0028] [Diagram 2] 1 is a schematic diagram illustrating a method for manufacturing a separator for a secondary battery according to an embodiment of the present invention.
[0029] [Diagram 3] 2 is a scanning electron microscope (SEM) photograph of the separation membranes according to Comparative Example 1 and Example 1.
[0030] [Figure 4a] 1 is a photograph showing the uniformity of the thickness of a coating layer included in a separator test piece according to Comparative Example 1. [Figure 4b] 1 is a photograph showing the uniformity of the thickness of a coating layer included in a separator test piece according to Comparative Example 2. [Figure 4c] 1 is a photograph showing the uniformity of the thickness of a coating layer included in a separator test piece according to Example 1. [Figure 4d]1 is a photograph showing the uniformity of the thickness of a coating layer included in a separator test piece according to Example 2. [Figure 4e] 1 is a photograph showing the uniformity of the thickness of a coating layer included in a separator test piece according to Example 3. [Figure 4f] 1 is a photograph showing the uniformity of the thickness of a coating layer included in a separator test piece according to Example 4. [Figure 4g] 1 is a photograph showing the uniformity of the thickness of a coating layer included in a separator test piece according to Example 5. [Figure 4h] 1 is a photograph showing the uniformity of the thickness of a coating layer included in a separator test piece according to Example 6.
[0031] [Figure 5a] 1 is a photograph of a separator according to Comparative Example 1 into which an electrolyte solution has been poured. [Figure 5b] 1 is a photograph of a separator according to Comparative Example 2 into which an electrolyte solution has been poured. [Figure 5c] 1 is a photograph of the separator according to Example 1 into which an electrolyte solution has been poured. [Figure 5d] 1 is a photograph of the separator according to Example 2 into which an electrolyte solution has been poured. [Figure 5e] 1 is a photograph of the separator according to Example 3 into which an electrolyte solution has been poured. [Figure 5f] 1 is a photograph of the separator according to Example 4 into which an electrolyte solution has been poured. [Figure 5g] 1 is a photograph of the separator according to Example 5 into which an electrolyte solution has been poured. [Figure 5h] 1 is a photograph of the separator according to Example 6 into which an electrolyte solution has been poured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Hereinafter, each component of the present invention will be described in more detail so that a person having ordinary knowledge in the technical field to which the present invention belongs can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.
[0033] In the present specification, the term "layer" or film may include a case where the layer or film is formed on the entire area when the area where the layer or film is present is observed, as well as a case where the layer or film is formed on only a part of the area. For example, the surface of the layer or film may be defined as including a flat form, a non-flat form, and a combination thereof; or a continuous form, a discontinuous form, and a combination thereof. For example, when another member is formed of a layer or film directly on one member, the coverage of the other member with respect to the one member may be defined as 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, 90% or more, 95% or more, or 99% or more.
[0034] In the present specification, the "weight average molecular weight" or "number average molecular weight" may be analyzed using a gel permeation chromatography (GPC) device as a standard polystyrene-equivalent molecular weight. Here, the GPC analysis method may be performed under the following analytical conditions: tetrahydrofuran may be used as a developing solvent, a sample concentration of 5 mg / mL, a sample introduction amount of 100 μl, a temperature of 40° C., and a flow rate of 1 mL / min.
[0035] According to one aspect of the present invention, there is provided a separator for a secondary battery, comprising: a porous substrate; and a functional coating layer disposed on at least one surface of the porous substrate, the functional coating layer comprising a first coating layer and a second coating layer disposed on the first coating layer, the first coating layer comprising inorganic particles, an acrylic binder, and polydopamine, and the second coating layer comprising polydopamine.
[0036] According to one aspect of the present invention, the first coating layer can significantly increase the loading amount of polydopamine for a combination of a fluorine-based binder and polydopamine by undergoing a condensation reaction between the amine group of polydopamine and the functional group of an acrylic binder. As a result, a separator for a secondary battery having improved dimensional stability at high temperatures in a wet state after an electrolyte is injected can be provided. When a secondary battery is realized using such a separator for a secondary battery, the problem of electrodes being exposed due to thermal shrinkage of the separator under high temperature conditions can be solved.
[0037] According to another aspect of the present invention, the second coating layer containing polydopamine can prevent the acrylic binder contained in the first coating layer from being immediately exposed to the electrolyte, thereby allowing a condensation reaction between the functional group of the acrylic binder and the amine group of the polydopamine to proceed sufficiently, thereby providing a separator for a secondary battery having improved dimensional stability at high temperatures in a wet state when the electrolyte is injected. If the second coating layer containing polydopamine is not present, the acrylic binder of the first coating layer may be immediately exposed to the electrolyte, and the condensation reaction between the acrylic binder and polydopamine may not proceed sufficiently, which may result in insufficient dimensional stability effect in a wet state when the electrolyte is injected.
[0038] The configuration of the present invention will be described in further detail below.
[0039] 1. Separation membrane for secondary batteries
[0040] The separator for a secondary battery according to the present invention includes a porous substrate and a functional coating layer.
[0041] porous substrate
[0042] The porous substrate according to the present invention can provide a path for lithium ions to move while electrically insulating the negative electrode and the positive electrode to prevent short circuits, and can be a porous structure having high resistance to an electrolyte and fine pores.
[0043] The material of the porous substrate is not particularly limited as long as it is an organic or inorganic material having electrical insulation. The porous substrate may include at least one selected from the group consisting of polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene, and specifically may include polyolefin. Polyolefin has excellent coating properties and can reduce the thickness of the separator to increase the proportion of the electrode active material layer in the battery, thereby increasing the capacity per volume. Specifically, the weight average molecular weight (M w ) may be 100,000 to 500,000 g / mol. If the weight average molecular weight of the polyolefin is less than the above range, it may be difficult to secure sufficient mechanical properties, and if it exceeds the above range, the shutdown function may not be realized or molding may be difficult. The shutdown function refers to the function of blocking the movement of ions and preventing thermal runaway of the battery by dissolving the thermoplastic resin and closing the pores of the porous substrate when the temperature of the secondary battery increases.
[0044] The thickness of the porous substrate may be, for example, 3 to 12 μm or 5 to 12 μm. If the thickness of the porous substrate is less than the above range, the conductive barrier function may be insufficient, and if the thickness exceeds the above range, the resistance of the separator may be excessively increased.
[0045] The average diameter of the pores in the porous substrate may be, for example, 10 to 100 nm. The pores in the porous substrate have an interconnected structure, allowing gas or liquid to pass from one side of the porous substrate to the other side.
[0046] The porosity of the porous substrate is not particularly limited, but may be, for example, 10 to 95%.
[0047] At least one surface of the porous substrate according to the present invention may be coated with polydopamine. For example, at least one surface of the porous substrate may be an open surface of the porous substrate and exposed to the outside. By coating at least one surface of the porous substrate with polydopamine, the wettability of the porous substrate to the electrolyte may be improved, and the impregnation ability of the electrolyte may be improved, thereby realizing a secondary battery with low resistance and high output and capacity.
[0048] Functional Coating Layer
[0049] The functional coating layer according to the present invention can improve the dimensional stability in a wet state in which an electrolyte is injected, and can enhance the mechanical strength and ion conductivity performance of the separator.
[0050] The functional coating layer according to the present invention is disposed on at least one surface of the porous substrate, that is, the functional coating layer according to one embodiment of the present invention may be disposed on one surface of the porous substrate, and the functional coating layer according to another embodiment of the present invention may be disposed on both surfaces of the porous substrate.
[0051] The functional coating layer according to the present invention includes polydopamine. Polydopamine according to one aspect of the present invention is included in the functional coating layer and can effectively prevent thermal shrinkage of the separator caused by high temperature conditions when the separator is in a wet state after the electrolyte is injected. Polydopamine according to another aspect of the present invention also has adhesive properties, so it can effectively prevent detachment of inorganic particles included in the functional coating layer and can provide strong adhesive properties to the interface between the electrode and the separator, thereby allowing lithium ions to be efficiently transferred.
[0052] Specifically, the decomposition temperature (T d ) may be 280 to 320°C, more specifically 290 to 320°C, more specifically 300 to 310°C. The decomposition temperature of the polydopamine may be analyzed by thermogravimetric analysis (TGA). When the decomposition temperature of the polydopamine satisfies the above numerical range, the dimensional stability of the separator in a wet state under high temperature conditions can be improved, and at the same time, the detachment of inorganic particles can be effectively prevented, and strong adhesive force can be imparted to the interface between the electrode and the separator, thereby effectively transferring lithium ions.
[0053] Specifically, the molecular weight of the polydopamine may be 1 to 1,000 kDa, more specifically, 100 to 1,000 kDa. When the molecular weight of the polydopamine is within the above range, the dimensional stability of the separator on the electrolyte under high temperature conditions can be improved and at the same time, the detachment of inorganic particles can be effectively prevented. For example, the molecular weight of the polydopamine can be analyzed by GPC (Gel permeation chromatography).
[0054] The loading amount of polydopamine contained in the functional coating layer according to the present invention is 0.1 g / m 2 It can be more than 1.0g / m 2 More specifically, it can be 1.5 g / m 2 It can be equal to or greater than 1.9 g / m2 When the loading amount of polydopamine contained in the functional coating layer is within the above range, the dimensional stability of the separator in a wet state under high temperature conditions can be improved. For example, the loading amount of polydopamine can be measured by a gravimetric analysis method using a gravimetric analysis device commonly used in the art.
[0055] The acrylic binder according to one aspect of the present invention may be a particle-type binder, which has low solubility in a solvent of a composition for forming a coating layer and exists in a particle state. The acrylic binder is contained in the functional coating layer together with polydopamine, thereby further increasing the loading amount of polydopamine and further enhancing the function of polydopamine. Conventionally, a coating layer prepared by mixing a fluorine-based binder with polydopamine has a low loading amount of polydopamine, and a problem occurs in which a separator in a wet state is thermally contracted under high temperature conditions, resulting in exposure of electrodes. The functional coating layer according to the present invention includes both an acrylic binder and polydopamine, thereby inducing a condensation reaction between the acrylic binder and polydopamine, thereby further increasing the loading amount of polydopamine in the separator. This makes it possible to easily solve the problem of electrodes being exposed due to thermal contraction of the separator in a wet state when an electrolyte is injected. For example, the particulate binder may have a solubility in the solvent of the composition for forming a coating layer of 1 g / 100 mL or less, 0.1 g / 100 mL or less, or 0.01 g / 100 mL or less.
[0056] The acrylic binder according to another aspect of the present invention can provide a bonding force between the porous substrate and the functional coating layer, and can help form a surface bond or point bond structure between a plurality of inorganic particles contained in the functional coating layer, thereby preventing the inorganic particles from being detached from the coating layer.
[0057] The glass transition temperature (T g) may be −20 to 80° C., specifically 30 to 80° C., and more specifically 50 to 80° C. When the glass transition temperature of the acrylic binder is within the above range, the loading amount of polydopamine can be further increased by combining the acrylic binder with polydopamine.
[0058] The weight average molecular weight (M w The weight average molecular weight (M) of the acrylic binder may be 100,000 to 2,000,000 g / mol, specifically 500,000 to 2,000,000 g / mol, and more specifically 500,000 to 1,000,000 g / mol. w ) falls within the above-mentioned range, the loading amount of polydopamine can be further increased by the combination of an acrylic binder and polydopamine.
[0059] For example, the acrylic binder may include a repeating unit derived from (meth)acrylate or (meth)acrylic acid, and specifically may be polymethylmethacrylate, polybutylacrylate, polyacrylic acid, etc. The functional group (ester group or carboxyl group) of the acrylic binder may undergo a condensation reaction with the amine group of polydopamine. This can further increase the loading amount of polydopamine in the functional coating layer.
[0060] FIG. 1 is a cross-sectional view of a separator for a secondary battery according to one embodiment of the present invention.
[0061] Referring to FIG. 1, the functional coating layer 20 according to the present invention includes a first coating layer 20a and a second coating layer 20b disposed on the first coating layer 20a. The first coating layer 20a may be disposed directly on the porous substrate 10, and the second coating layer 20b may be disposed directly on the first coating layer 20a. That is, the first and second coating layers 20a and 20b may be formed continuously or separately. The second coating layer is disposed on the first coating layer, so that the acrylic binder included in the first coating layer is prevented from being immediately exposed to the electrolyte, and thus, a condensation reaction between the functional group of the acrylic binder and the amine group of polydopamine is sufficiently progressed, thereby providing a separator 100 for a secondary battery having improved dimensional stability at high temperatures in a wet state in which the electrolyte is injected. If the second coating layer containing polydopamine were not present, the acrylic binder of the first coating layer would be immediately exposed to the electrolyte, and the condensation reaction between the acrylic binder and polydopamine may not proceed sufficiently, which may result in the dimensional stability effect not being fully realized in a wet state after the electrolyte is injected.
[0062] For example, the thickness of the first coating layer 20a may be 0.1 to 5 μm, more specifically 1 to 3 μm, and the thickness of the second coating layer 20b may be 0.005 to 0.05 μm, more specifically 0.01 to 0.03 μm.
[0063] According to yet another embodiment of the present invention, the thickness ratio (second coating layer:first coating layer) of the second coating layer 20b to the first coating layer 20a may be 1:2 to 1:1,000, specifically 1:50 to 1:150. When the thickness ratio of the second coating layer to the first coating layer satisfies the above numerical range, the dimensional stability of the separator in a wet state in which an electrolyte is injected under high temperature conditions can be improved, and strong adhesive force can be imparted to the interface between the electrode and the separator, thereby effectively transferring lithium ions.
[0064] The first coating layer 20a according to the present invention includes inorganic particles that contribute to improving the mechanical strength and heat resistance of the separator for a secondary battery.
[0065] Specifically, the inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in the present invention are those that can be used in the operating voltage range (e.g., Li / Li + There are no particular limitations as long as the oxidation and / or reduction reaction does not occur at a reference voltage of 0 to 5 V.
[0066] For example, when inorganic particles having a high dielectric constant are used as the inorganic particles, the inorganic particles can contribute to increasing the dissociation degree of the electrolyte salt, for example, the lithium salt, in the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte. For the above reasons, the inorganic particles may be inorganic particles having a dielectric constant of 5 or more, inorganic particles having lithium ion transfer ability, or a mixture thereof.
[0067] The inorganic particles having a dielectric constant of 5 or more are Al2O3, SiO2, ZrO2, AlO(OH), Al(OH)3, Mg(OH)2, BaSO4, TiO2, BaTiO3, Pb(Zr x Ti 1-x )O3(PZT, where 0 <x<1)、Pb 1-x La x Zr 1-y Ti y O3(PLZT, where 0 <x<1,0<y<1である)、(1-x)Pb(Mg 1 / 3 Nb2 / 3 )O 3-x It may be one or more mixtures selected from the group consisting of PbTiO3 (PMN-PT, where 0 < x < 1), HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, and SiC.
[0068] The inorganic particles having the lithium ion transfer ability are lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4) and P2S5-based glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7) and may be one or more mixtures selected from the group consisting of.
[0069] For example, the average particle size (D 50 ) of the inorganic particles can be from 1 nm to 4 μm, specifically from 10 nm to 2 μm, and more specifically from 50 nm to 1 μm for the formation of a coating layer with a uniform thickness and an appropriate porosity. The "average particle size (D 50)" refers to the particle size at the 50% point of the cumulative particle number distribution according to the particle size. The average particle size can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then the dispersion medium is introduced into a commercially available laser diffraction particle size measuring device (e.g. Microtrac S3500). When the particles pass through a laser beam, the difference in the diffraction pattern according to the particle size is measured, and the particle size distribution can be calculated.
[0070] According to another embodiment of the present invention, the second coating layer 20b may be made of polydopamine without including inorganic particles and an acrylic binder. The presence of the second coating layer can significantly improve the dimensional stability of the separator on the electrolyte.
[0071] The polydopamine of the first coating layer 20a according to the present invention may be coated on at least one of the surfaces of the acrylic binder and the inorganic particles, specifically, on the surfaces of the acrylic binder and the inorganic particles. By coating the surfaces of the acrylic binder and the inorganic particles with the polydopamine, a condensation reaction is induced between the polydopamine coated on the surfaces of the inorganic particles and the acrylic binder, thereby effectively preventing the inorganic particles from being detached.
[0072] 2. Manufacturing method of separator for secondary battery
[0073] FIG. 2 is a schematic diagram illustrating a method for manufacturing a separator for a secondary battery according to an embodiment of the present invention.
[0074] 2, the preliminary separation membrane before dip coating may include a porous substrate 10, and inorganic particles 24 and an acrylic binder 22 on the porous substrate 10. When the preliminary separation membrane is immersed in a dopamine precursor solution, polydopamine 26 may be coated on at least one of the acrylic binder 22, the inorganic particles 24, and the porous substrate 10.
[0075] (S1) Stage: Pre-separation membrane (CCS) soaking stage
[0076] Referring to FIG. 2, the method for preparing a separator for a secondary battery according to the present invention may include (S1) immersing a preliminary separator including a porous substrate and a first coating layer disposed on at least one surface of the porous substrate in a dopamine precursor solution for 4 to 50 hours.
[0077] The dopamine precursor solution may be, for example, a mixture of dopamine and an alkaline buffer solution. The dopamine may be converted to polydopamine through a cyclization reaction by an oxidation process without an initiator, and then a polymerization reaction, as shown in Reaction Scheme 1 below.
[0078] [Reaction Scheme 1]
[0079] [ka]
[0080] The pH of the dopamine precursor solution may be 7 to 10, specifically 7 to 9, more specifically 7.5 to 8.5, more specifically 7.8 to 8.2, and more specifically 7.9 to 8.1. When the pH of the dopamine precursor solution is within the above range, the loading amount of polydopamine in the functional coating layer may be sufficiently increased and polydopamine may be uniformly distributed. The pH of the dopamine precursor solution may be changed by adjusting the concentration of the alkaline buffer solution.
[0081] Specifically, the time for immersing the preliminary separation membrane in the dopamine precursor solution may be 4 to 48 hours, more specifically 12 to 48 hours, more specifically 40 to 48 hours, or 46 to 48 hours. When the time for immersing the preliminary separation membrane in the dopamine precursor solution is within the above range, the loading amount of polydopamine in the functional coating layer may be sufficiently increased, and the uniformity of the coating layer may be improved.
[0082] The preliminary separator may have, for example, a CCS (Ceramic Coated Separator) structure commonly used in the relevant technical field.
[0083] Step (S2): forming a second coating layer;
[0084] The method for manufacturing a separator for a secondary battery according to the present invention may include (S2) forming a second coating layer on at least one surface of the preliminary separator by adjusting the amount of dissolved oxygen in the dopamine precursor solution in which the preliminary separator is immersed.
[0085] As a means for controlling the amount of dissolved oxygen in the dopamine precursor solution in which the preliminary separation membrane is immersed, for example, a method of controlling the degree of opening and closing of a reaction vessel can be used. Since an oxidation process of exposure to oxygen is required for the polymerization reaction to polydopamine in the dopamine precursor solution, the amount of dissolved oxygen in the dopamine precursor solution can affect the synthesis reaction of polydopamine.
[0086] Specifically, the amount of dissolved oxygen contained in the dopamine precursor solution in which the preliminary separation membrane is immersed may be 8.0 to 11.0 ppm, specifically 8.0 to 10.0 ppm, and more specifically 8.0 to 9.0 ppm. When the amount of dissolved oxygen contained in the dopamine precursor solution in which the preliminary separation membrane is immersed is within the above numerical range, polydopamine that can increase the loading amount of polydopamine in the functional coating layer can be easily synthesized. As an analytical method for measuring the amount of dissolved oxygen, for example, the Winkler-Azide modification using manganese sulfate and alkaline potassium iodide sodium azide solution can be used.
[0087] According to one embodiment of the present invention, by deriving an optimal combination of process parameters, including the pH of the dopamine precursor solution, the time for immersing the preliminary separation membrane in the dopamine precursor solution, and the degree of oxygen exposure (e.g., the amount of dissolved oxygen in the dopamine precursor solution), the loading amount of polydopamine in the functional coating layer can be increased to provide a separation membrane with excellent dimensional stability even at high temperatures in a wet state.
[0088] According to another embodiment of the present invention, the step (S2) may include a step of drying the preliminary separation membrane immersed in the dopamine precursor solution to induce a condensation reaction between polydopamine and an acrylic binder. Specifically, the step (S2) may include a step of drying the preliminary separation membrane immersed in the dopamine precursor solution under vacuum conditions at 60 to 80° C. for 4 to 8 hours, and more specifically, a step of drying at 60 to 70° C. for 5 to 7 hours. When the drying temperature and drying time range of the preliminary separation membrane immersed in the dopamine precursor solution are satisfied, the condensation reaction between the acrylic binder and polydopamine can be sufficiently progressed.
[0089] 3. Secondary battery
[0090] Other embodiments of the present invention can provide a secondary battery including a negative electrode, a positive electrode, a separator for the secondary battery interposed between the negative electrode and the positive electrode, and an electrolytic solution. Repeated descriptions of the above-mentioned parts will be briefly described or omitted.
[0091] negative electrode
[0092] The negative electrode according to the present invention can include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer can include a negative electrode active material, a conductive material, and a negative electrode binder.
[0093] The negative electrode current collector can function as a path for transmitting electrons from the outside so that an electrochemical reaction occurs in the negative electrode active material or receiving electrons from the negative electrode active material and sending them to the outside. For example, as the negative electrode current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or a material obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. can be used. Specifically, a transition metal that adsorbs carbon well, such as copper or nickel, can also be used as the current collector. For example, the thickness of the negative electrode current collector can be 6 μm to 20 μm, but the thickness of the negative electrode current collector is not limited thereto.
[0094] The negative electrode active material can play a role of storing or releasing lithium ions and generating electricity. For example, as the negative electrode active material, at least one of silicon-based active material particles and graphite-based active material particles can be included.
[0095] The silicon-based active material particles are Si, SiO x (0 < x ≤ 2), Si-C composite, and Si-Y alloy (Y is any one element selected from the group consisting of an alkali metal, an alkaline earth metal, a transition metal, a Group 13 element, a Group 14 element, and a rare earth element), and one or more selected from the group can be used.
[0096] The graphite-based active material particles may include at least one selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and graphitized mesocarbon microbeads.
[0097] The content of the negative active material may be 80 to 97 wt % based on the total solid content in the negative active material layer.
[0098] The conductive material can improve the conductivity between active material particles or between the active material particles and the metal current collector in the electrode and prevent the binder from acting as a non-conductor. The conductive material can be, for example, one or a mixture of two or more conductive materials selected from the group consisting of graphite, carbon black, carbon fiber, metal fiber, metal powder, conductive whiskers, conductive metal oxide, activated carbon, and polyphenylene derivatives, and more specifically, one or a mixture of two or more conductive materials selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide.
[0099] The negative electrode binder can suppress separation between negative electrode active material particles or between the negative electrode and the current collector. As the negative electrode binder, a polymer commonly used in electrodes in the relevant technical field can be used. Such negative electrode binders include, but are not limited to, poly(vinylidene fluoride co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), poly(methylmethacrylate), poly(ethylhexylacrylate), poly(butylacrylate), poly(acrylonitrile), poly(vinylpyrrolidone), poly(vinyl acetate), poly(ethylene-co-vinyl acetate), poly(ethylene oxide), polyarylate, cellulose acetate, and cellulose acetate butyrate. Examples of the cellulose acetate copolymer include, but are not limited to, cellulose acetate propionate, cyano ethyl pullulan, cyano ethyl poly(vinylalcohol), cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxyl methyl cellulose.
[0100] positive electrode
[0101] The positive electrode according to the present invention may include a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer may include a positive electrode active material, a conductive material, and a positive electrode binder.
[0102] For example, the positive electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery. Specifically, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. The positive electrode current collector may typically have a thickness of 6 to 20 μm.
[0103] For example, the positive electrode active material may include a lithium transition metal oxide. x1 CoO2(0.5 <x1<1.3)、Li x2 NiO2(0.5 <x2<1.3)、Li x3 MnO2(0.5 <x3<1.3)、Li x4 Mn2O4(0.5 <x4<1.3)、Li x5 (Ni a1 Co b1 Mn c1 )O2(0.5 <x5<1.3,0<a1<1,0<b1<1,0<c1<1、a1+b1+c1=1)、Li x6 Ni 1-y1 Co y1 O2(0.5 <x6<1.3,0<y1<1)、Li x7 Co 1-y2 Mn y2 O2(0.5 <x7<1.3,0≦y2<1)、Li x8 Ni 1-y3 Mn y3 O2(0.5 <x8<1.3、O≦y3<1)、Li x9 (Ni a2 Co b2 Mn c2 )O4(0.5 <x9<1.3,0<a2<2,0<b2<2,0<c2<2,a2+b2+c2=2)、Li x10Mn 2-z1 Ni z1 O4 (0.5 < x10 < 1.3, 0 < z1 < 2), Li x11 Mn 2-z2 Co z2 O4 (0.5 < x11 < 1.3, 0 < z2 < 2), Li x12 CoPO4 (0.5 < x12 < 1.3) and Li x13 It may be any one or more selected from the group consisting of FePO4 (0.5 < x13 < 1.3).
[0104] The conductive material used for the positive electrode may be the same as or different from the conductive material used for the negative electrode.
[0105] The positive electrode binder may be the same as or different from the negative electrode binder.
[0106] electrolyte
[0107] The electrolytic solution according to the present invention can contain a solvent and a lithium salt.
[0108] Solvents according to the invention are, for example, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl methyl carbonate (EMC), gamma-butyrolactone (GBL), fluoroethylene carbonate (Fluoroethylene carbonate), tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl methyl carbonate (EMC), gamma-butyrolactone (GBL), fluoroethylene carbonate (Fluoroethylene carbonate), tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl methyl carbonate (EMC), tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl methyl carbonate (TMC ... The alkyl group may be one or a mixture of two or more selected from the group consisting of methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, pentyl acetate, methyl propionate, ethyl propionate, ethyl propionate, and butyl propionate.
[0109] The lithium salt according to the invention is, for example, NO3 - , F - , Cl - , Br - , I - , PF6 - The anions may include, for example,
[0110] The secondary battery according to the present invention may be a cylindrical, square, or pouch-shaped secondary battery, and is not particularly limited as long as it corresponds to a charge / discharge device.
[0111] According to yet another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery pack can be used as a power source for at least one medium-sized or large-sized device selected from the group consisting of a power tool, an electric vehicle (EV), a hybrid electric vehicle (HEV), and an electric vehicle (PHEV), including a plug-in hybrid electric vehicle (PHEV), or a power storage system.
[0112] Hereinafter, an embodiment of the present invention will be described in detail so that a person having ordinary skill in the art to which the present invention belongs can easily carry out the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content.
[0113] [Production Example 1: Production of separator for secondary battery]
[0114] <Comparative Example 1: Production of CCS separation membrane>
[0115] The glass transition temperature is 80°C and the weight average molecular weight (M w An acrylic particle-type binder (polymethyl methacrylate) with an average particle diameter (D) of 500,000 g / mol was added to a solvent (water) and dissolved at 25° C. for 2 hours to prepare a polymer solution (solid content = 35 wt%). 50 After adding inorganic particles (Al2O3) having a particle size of 0.5 μm, the inorganic particles were crushed and pulverized in a ball mill for more than 12 hours to prepare a composition for forming a first coating layer in which the acrylic particle type binder and inorganic particles (Al2O3) were mixed in a weight ratio of 1:9.
[0116] The composition for forming the first coating layer was applied to both sides of a polyethylene porous substrate having a thickness of 10 μm and a porosity of 48% by a slot-die coating method, and then dried at 60° C. for 5 minutes to form a first coating layer having a thickness of 1.5 μm (loading amount of inorganic particles: 2.7 g / m 2 As a result, a preliminary separator (Ceramic Coated Separator; CCS) with a total thickness of 13 μm was manufactured.
[0117] Example 1: Dopamine precursor solution pH=8 / immersion for 48 hours / container partially open
[0118] Dopamine was dissolved in an alkaline buffer solution (20 mM Tris-HCl buffer) at a concentration of 2 mg / mL using a Petri dish, and the lid of the Petri dish was partially opened to prepare a dopamine precursor solution with a pH of 8 (dissolved oxygen content = 8 ppm). The preliminary separator (CCS) according to Comparative Example 1 was immersed in the dopamine precursor solution for 48 hours and then dried under vacuum conditions at 60°C for 6 hours to finally prepare a separator for a secondary battery. By drying the preliminary separator immersed in the dopamine precursor solution, a condensation reaction was induced between the ester group of polymethyl methacrylate and the amine group of polydopamine.
[0119] <Comparative Example 2: When a fluorine-based binder was used, unlike Example 1>
[0120] A preliminary separator according to Comparative Example 2 was prepared in the same manner as in Comparative Example 1, except that a poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) binder having a weight average molecular weight of 500,000 g / mol and a content of HFP-derived units of 14 wt% was used instead of the acrylic binder.
[0121] Thereafter, a separator for a secondary battery according to Comparative Example 2 was produced in the same manner as in Example 1, but the preliminary separator according to Comparative Example 2 was used instead of the preliminary separator according to Comparative Example 1.
[0122] <Comparative Example 3: Preparation of a separation membrane without a second coating layer unlike Example 1>
[0123] The same Al2O3 (average particle size (D 50 30g of polydopamine (0.5μm) was mixed with 2g of dopamine and stored at 20℃ for 4 hours to induce the autopolymerization reaction of dopamine. After that, the mixture was repeatedly ultrasonically washed with secondary distilled water according to the medium removal method and completely dried at 50℃ to obtain inorganic particles with a polydopamine coating layer (thickness: 20nm) formed on the surface.
[0124] A separation membrane according to Comparative Example 3 was prepared in the same manner as in Comparative Example 1, except that the inorganic particles having a polydopamine coating layer formed on the surface thereof were used instead of the inorganic particles of Comparative Example 1. As a result, the separation membrane according to Comparative Example 3 does not have a second coating layer.
[0125] <Example 2: Unlike Example 1, pH of dopamine precursor solution = 7 / immersed for 24 hours / all containers closed>
[0126] A dopamine precursor solution having a pH of 7 was prepared by adjusting the concentration of the alkaline buffer solution, and the polydopamine polymerization reaction was carried out under oxygen-blocking conditions in which the Petri dishes were all closed. A separator for a secondary battery was prepared in the same manner as in Example 1, except that the immersion time of the preliminary separator was changed to 24 hours.
[0127] <Example 3: Partial opening of container unlike Example 2>
[0128] A separator for a secondary battery was prepared in the same manner as in Example 2, except that the Petri dish was partially opened to prepare a dopamine precursor solution (dissolved oxygen content=8 ppm).
[0129] <Example 4: Unlike Example 2, the container is completely opened>
[0130] A separator for a secondary battery was prepared in the same manner as in Example 2, except that the Petri dishes were all opened and a dopamine precursor solution (dissolved oxygen content=9 ppm) was prepared.
[0131] <Example 5: Unlike Example 1, when the immersion time was changed to 24 hours>
[0132] A separator for a secondary battery was manufactured in the same manner as in Example 1, but the preliminary separator (CCS) according to Comparative Example 1 was immersed in the dopamine precursor solution for 24 hours instead of 48 hours.
[0133] <Example 6: Different from Example 5, when the pH of the dopamine precursor solution is 9>
[0134] A separator for a secondary battery was produced in the same manner as in Example 5, but the pH of the dopamine precursor solution was changed to 9.
[0135] [Table 1]
[0136] [Experimental Example 1: Analysis of polydopamine loading amount in functional coating layer] The polydopamine loading amount for the separation membrane specimens (size: 50 mm x 50 mm) according to Comparative Examples 1 to 3 and Examples 1 to 6 was analyzed by a weight measurement method using a weight analysis device under ambient conditions.
[0137] [Table 2]
[0138] Referring to Tables 1 and 2, it can be seen that the three factors of the pH of the dopamine precursor solution, the degree of opening and closing of the container (degree of oxygen exposure), and the time for which the preliminary separation membrane is immersed in the dopamine precursor solution (immersion time) all have a complex effect on the loading amount of polydopamine. In particular, as in Examples 1 and 5, when the pH of the dopamine precursor solution is 8, the container is partially opened, and the immersion time is set to 24 to 48 hours, the loading amount of polydopamine is 1.0 g / m 2 In terms of the loading amount of polydopamine, when Comparative Example 2 is compared with Example 1, it can be seen that the loading amount of polydopamine is significantly higher when an acrylic binder is combined with polydopamine than when a fluorine-based binder is combined with polydopamine.
[0139] [Experimental Example 2: SEM photos of separation membranes according to Comparative Example 1 and Example 1]
[0140] FIG. 3 is a scanning electron microscope (SEM) photograph of the separation membranes according to Comparative Example 1 and Example 1.
[0141] Referring to FIG. 3, it can be seen that a functional coating layer containing polydopamine was introduced into the separator of Example 1.
[0142] [Experimental Example 3: Evaluation of membrane thickness uniformity]
[0143] The thickness uniformity of the coating layer included in the separator test pieces (size: 50 mm×50 mm) according to Comparative Examples 1 and 2 and Examples 1 to 6 was observed with the naked eye.
[0144] FIG. 4a is a photograph showing the uniformity of the thickness of the coating layer included in the separation membrane specimen according to Comparative Example 1. FIG. 4b is a photograph showing the uniformity of the thickness of the coating layer included in the separation membrane specimen according to Comparative Example 2. FIG. 4c is a photograph showing the uniformity of the thickness of the coating layer included in the separation membrane specimen according to Example 1. FIG. 4d is a photograph showing the uniformity of the thickness of the coating layer included in the separation membrane specimen according to Example 2. FIG. 4e is a photograph showing the uniformity of the thickness of the coating layer included in the separation membrane specimen according to Example 3. FIG. 4f is a photograph showing the uniformity of the thickness of the coating layer included in the separation membrane specimen according to Example 4. FIG. 4g is a photograph showing the uniformity of the thickness of the coating layer included in the separation membrane specimen according to Example 5. FIG. 4h is a photograph showing the uniformity of the thickness of the coating layer included in the separation membrane specimen according to Example 6.
[0145] 4a to 4h, it was confirmed with the naked eye that the thickness uniformity of the coating layer included in the separators of Examples 1 to 6 was superior to that of Comparative Examples 1 and 2. In particular, it was confirmed that the thickness uniformity of the coating layer was significantly reduced in the case of Comparative Example 2 in which a fluorine-based binder and polydopamine were combined.
[0146] [Manufacturing Example 2: Manufacturing of a secondary battery replica sample]
[0147] A sample pouch was prepared by injecting one 5cm*5cm separator and 1g of mobile electrolyte into a 10cm*9cm three-sided sealing Al pouch and sealing the top. The mobile electrolyte was prepared by dissolving 1M LiPF6 in a carbonate-based mixed solvent in which ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 1:1.
[0148] [Experimental Example 4: Evaluation of wet thermal shrinkage at high temperatures]
[0149] The sample pouch according to Preparation Example 2 was stored in a convection oven at 135° C. for 30 minutes, and then the dimension in the transverse direction (TD) was measured. Then, the wet heat shrinkage rate of the separator was calculated according to the following Equation 1. The calculation results are shown in Table 3 below.
[0150] FIG. 5a is a photograph of the separation membrane according to Comparative Example 1 into which an electrolyte solution has been injected. FIG. 5b is a photograph of the separation membrane according to Comparative Example 2 into which an electrolyte solution has been injected. FIG. 5c is a photograph of the separation membrane according to Example 1 into which an electrolyte solution has been injected. FIG. 5d is a photograph of the separation membrane according to Example 2 into which an electrolyte solution has been injected. FIG. 5e is a photograph of the separation membrane according to Example 3 into which an electrolyte solution has been injected. FIG. 5f is a photograph of the separation membrane according to Example 4 into which an electrolyte solution has been injected. FIG. 5g is a photograph of the separation membrane according to Example 5 into which an electrolyte solution has been injected. FIG. 5h is a photograph of the separation membrane according to Example 6 into which an electrolyte solution has been injected.
[0151] [Formula 1]
[0152] Wet heat shrinkage rate of separation membrane = [(L i -L f ) / L i )] x 100
[0153] In the above formula 1, L i is the length before contraction in the lateral direction, L f is the length after contraction in the lateral direction.
[0154] [Table 3]
[0155] 5a to 5h, it can be seen that the wet heat shrinkage of the separator is low under high temperature conditions when the pH of the dopamine precursor solution is 8, the container is partially opened, and the immersion time is adjusted to 24 to 48 hours as in Examples 1 and 5. Comparing Comparative Example 2 with Example 1 in terms of the binder, it can be seen that the heat shrinkage of the separator is significantly lower at high temperature and in a wet state where the electrolyte is injected when an acrylic binder is combined with polydopamine compared to a combination of a fluorine-based binder with polydopamine. This is presumably due to the fact that the loading amount of polydopamine is significantly increased when a condensation reaction occurs between the functional group of the acrylic binder and the amine group of polydopamine in the combination of a fluorine-based binder with polydopamine.
[0156] Comparing Comparative Example 3 and Example 1 in terms of the wet heat shrinkage rate of the separator at high temperatures depending on the presence of the second coating layer containing polydopamine, it can be seen that Comparative Example 3, which uses inorganic particles coated on the surface with polydopamine, has an increased wet heat shrinkage rate at high temperatures, whereas Example 1, which has a second coating layer containing polydopamine, has a significantly decreased heat shrinkage rate of the separator at high temperatures and in a wet state when an electrolyte is injected. Therefore, even if inorganic particles with a polydopamine coating layer formed on the surface are simply used, in the absence of a second coating layer, the effect of reducing the wet heat shrinkage rate of the separator may not be achieved.
[0157] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also belong to the scope of the present invention. [Explanation of symbols]
[0158] 10 Porous substrate
[0159] 20 Functional coating layer
[0160] 20a First coating layer
[0161] 20b Second coating layer
[0162] 100 Separation membrane for secondary batteries
Claims
1. A porous substrate; a functional coating layer disposed on at least one surface of the porous substrate; The functional coating layer is a first coating layer and a second coating layer disposed on the first coating layer; the first coating layer comprises inorganic particles, an acrylic binder, and polydopamine; the second coating layer comprises polydopamine; Separation membrane for secondary batteries.
2. At least one surface of the porous substrate is coated with polydopamine; The separator for a secondary battery according to claim 1 .
3. The second coating layer is made of polydopamine. The separator for a secondary battery according to claim 1 .
4. The polydopamine of the first coating layer is coated on at least one surface of the acrylic binder and the inorganic particles. The separator for a secondary battery according to claim 1 .
5. The thickness of the first coating layer is 0.1 to 5 μm; The thickness of the second coating layer is 0.005 to 0.05 μm. The separator for a secondary battery according to claim 1 .
6. The decomposition temperature of the polydopamine (T d ) is 280 to 320° C. The separator for a secondary battery according to claim 1 .
7. The glass transition temperature (T g ) is −20 to 80° C. The separator for a secondary battery according to claim 1 .
8. The weight average molecular weight (M w ) is 100,000 to 2,000,000 g / mol; The separator for a secondary battery according to claim 1 .
9. (S1) immersing a preliminary separation membrane including a porous substrate and a first coating layer disposed on at least one surface of the porous substrate in a dopamine precursor solution for 4 to 50 hours; (S2) controlling the amount of dissolved oxygen in the dopamine precursor solution in which the preliminary separation membrane is immersed to form a second coating layer on at least one surface of the preliminary separation membrane; the pH of the dopamine precursor solution is between 7 and 10; The first coating layer includes an acrylic binder. A method for manufacturing a separator for a secondary battery.
10. The amount of dissolved oxygen contained in the dopamine precursor solution in which the preliminary separation membrane is immersed is 8.0 to 11.0 ppm; The method for producing the separator for a secondary battery according to claim 9.
11. A negative electrode; A positive electrode and The separator for a secondary battery according to claim 1 , interposed between the negative electrode and the positive electrode; and an electrolyte; Secondary battery.
Citation Information
Patent Citations
Separator for lithium-sulfur battery having composite coating layer containing polydopamine, method for producing the same, and lithium-sulfur battery including the same
JP2018520490A
Modified ceramic separator composite and method for producing the same
JP2018528583A
Separator for lithium-sulfur battery and lithium-sulfur battery including the same
JP2020532841A